Identification and characterization of a spontaneous ovarian carcinoma in Lewis rats - Sharrow Allison C; Ronnett Brigitte M; Thoburn Christopher J; Barber James P; Giuntoli Robert L; Armstrong Deborah K; Jones Richard J; Hess Allan D (BMC, 2010)
Abstract Background Ovarian carcinoma is the fourth most common cause of death from cancer in women. Limited progress has been made toward improving the survival rate of patients with this disease in part because of the lack of a good animal model. We present here a model of spontaneous ovarian carcinoma arising in a normal Lewis rat. Methods A spontaneously occurring tumor of the left ovary was found in a normal Lewis rat during necropsy, which was sectioned for histological examination and placed into single cell suspension. Tumor cells were passaged in vivo by intraperitoneal injection into immunocompetent Lewis rats, and in vitro culture resulted in generation of a cell line. Tumor cells were examined by flow cytometry for expression of estrogen receptor α, progesterone receptor, androgen receptor, her-2/neu, epithelial cell adhesion molecule, and CA125. β-catenin expression and cellular localization was assessed by immunocytochemistry. RNA was harvested for gene expression profiling and studying the expression of cytokines. Results The tumor, designated FNAR, could be serially transplanted into Lewis rats and propagated as a cell line in vitro, maintaining the properties of the original tumor. The FNAR cells displayed striking morphologic similarities to human ovarian carcinoma, resembling the endometrioid carcinoma subtype of surface epithelial neoplasms. The cells expressed estrogen receptor α, progesterone receptor, androgen receptor, her-2/neu, epithelial cell adhesion molecule, CA125, and nuclear β-catenin. A gene expression profile showed upregulation of a number of genes that are also upregulated in human ovarian carcinoma. Conclusion This reliable model of ovarian carcinoma should be helpful in better understanding the biology of the disease as well as the development of novel treatment strategies.